The Spillover Effects of a Downturn in China's Real Estate Investment - Ahuja, Ashvin; Myrvoda, Alla. (Washington, D.C. : International Monetary Fund, 2012)
Real estate investment accounts for a quarter of total fixed asset investment (FAI) in China. The real estate sector's extensive industrial and financial linkages make it a special type of economic activity, especially where the credit creation process relies primarily on collateral, like in China. As a result, the impact on economic activity of a collapse in real estate investment in China-though a low-probability event-would be sizable, with large spillovers to a number of China's trading partners. Using a two-region factor-augmented vector autoregression model that allows for interaction between China and the rest of the G20 economies, we find that a 1-percent decline in China's real estate investment would shave about 0.1 percent off China's real GDP within the first year, with negative spillover impacts to China's G20 trading partners that would cause global output to decline by roughly 0.05 percent from baseline. Japan, Korea, and Germany would be among the hardest hit. In that event, commodity prices, especially metal prices, could fall by as much as 0.8-2.2 percent below baseline one year after the shock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet